Respostas psicofisiológicas em diferentes comandos de esforço durante caminhada em idosas - Peres, André Luís (2018)
Walking is considered a simple exercise and recommended as a beneficial strategy for the elderly population, there are still few studies that demonstrate the cognitive ability to discriminate different instructions of the exercise in order to reach the target intensity of training that guarantee benefits to physical and mental health. Objective: to compare psychophysiological responses and walking speed between spontaneous, selfselected and prescribed conditions in elderly women. Methods: Sixteen active elderly women participated in this study (66.9 ± 5.0 years). The study consisted of six 20- minute experimental sessions: 1. spontaneous (S), in which the elderly women walked at their usual speed, unaware that the research data were being collected; 2. selfselected (SS), in which participants were instructed to walk at "preferred / selected intensity", and their reproduction (SR); and 3. prescribed in which the elderly women were walking with easy effort (EE), moderate (ME) and difficult (DE); the last three three sessions were counterbalanced. Psychophysiological assessment (OMNI of Subjective Effort Perception and affective valence - Feeling Scale) and heart rate (HR) were measured immediately after exercise, and distance was recorded to calculate walking speed. The data description is presented through the mean and standard deviation. A one-way ANOVA examined differences between conditions and post-hoc Tukey was used to locate the differences (p <0.05). Results: Mean walking speed did not differ significantly between S (1.42±0.15 m/s), SS-SR (1.43±0.12 m/s) and ME (1.40±0,07 m/s). Significant differences were found between the condition of prescribed stress (EE: 1.14 ± 0.10 m/s, ME: 1.40±0.07 m/s, DE: 1.61±0.06 m/s). HR did not differ significantly between S, SS-SR and ME conditions (130.5±14.5 bpm, 136.2±7.8 bpm, 138.9±6.1 bpm and 138.6±5,1 bpm, respectively). Significant differences were found between the stress conditions prescribed as the elderly underwent conditions of increased effort. The relative intensity of the exercise, calculated by% FCres, did not differ between S (66±16.2%), SS-SR (73.5±12.1% and 76.4±10.5%, respectively) and ME (74.5±6.4%). Significant differences were found only between EE and ME, versus DE (85.1±7.9%). PSE differed between conditions S (6.2±1.7), SS-SR (6.2±0.9 and 6.5±0.8, respectively) and ME (6.1±0.8). Significant differences were found only between the condition of prescribed efforts (EE: 4.3±0.7, ME: 6.1±0.8, DE: 8.4±0.5). The affective valence remained stable and positive / pleasurable regardless of the experimental condition, that is, the intensity of exercise performed (variation between 4 and 5). Conclusion: Active elderly women were able to discriminate different commands prescribed in an exercise session aiming at easy, moderate and difficult physical exertion. Spontaneous and self-selected intensities caused walking velocities similar to those of the prescribed session with moderate effort. Public health strategies can use these simple effort instructions for prescribing moderate-intensity exercises and provide health benefits and pleasurable feelings which in turn can improve adherence to exercise programs.